Optimizing the refrigerants in ultra-low temperature Semiconductor processing chiller with mixed Refrigerant - Hye-In Jung; Chang-Hyo Son; Joon-Hyuk Lee (Case Studies in Thermal Engineering, 2024)
Mixed refrigerant (MR) Cascade Refrigeration Systems are widely employed in industries requiring both extremely low temperatures and large cooling capacity, such as semiconductors and displays. The composition of the MR has a significant impact on the performance of the cascade refrigeration systems, so optimizing the MR composition is essential. The current studies mainly focus on optimization that changes only the composition ratio with a limited number of refrigerants. Therefore, there may be a configuration and composition ratio that can improve the performance of the system more than existing methods. This study presents the need to find the optimal combination and number of MRs before determining the performance of MRs according to changes in composition. The proposed method selects five types of refrigerants that meet the conditions, then classifies cases according to the number of refrigerants in MR and analyzes the performance of each MR at various HTC evaporation temperatures based on energy and exergy through cycle simulation for each case. The proposed method showed COP up to 14.85 % higher than the conventional method, so it is expected to contribute to improving system performance by finding the optimal refrigerant combination and number before optimizing the composition of the MR.